Line x Tester analysis for yield and its related traits in rice (Oryza sativa I.) - Hossain, Kamal; Akter, A; Begum, H; Ansari, A; Rahman, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 1-6